Racehorse in the rain - Baglio, Ben M.; Baum, Ann (New York : Scholastic, 2004)
Mandy is thrilled when her dad wins first prize in the Christmas raffle and wins a racehorse for the day.
"A Working Partners book"--P. [4] of cover.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Christmas stories